Do Community-Driven Development Projects Enhance Social Capital? Evidence from the Philippines - Labonne, Julien (World Bank, Washington, DC, 2012)
This paper explores the social capital impacts of a large-scale, community-driven development project in the Philippines in which communities competed for block grants for infrastructure investment. The analysis uses a unique data set of about 2,100 households collected before the project started (2003) and after one cycle of sub-project implementation (2006) in 66 treatment and 69 matched control communities. Participation in village assemblies, the frequency with which local officials meet with residents and trust towards strangers increased as a result of the project. However, there is a decline in group membership and participation in informal collective action activities. This may have been because households were time-constrained, so that in order to participate in project activities, they needed to temporarily reduce their participation in informal activities. An alternative explanation is that the project improved the efficiency of formal forms of social capital and thus households needed to rely less on informal forms. Finally, the results indicate that, in the short run, the project might have reduced the number of other investments.